Verbal interaction in English and Filipino a study of classroom discourse in science and social studies in four grade levels - Mogol, Martha A. (1977)
The main objective of this study was to find out how well the two languages of instruction - English and Filipino - handle their functions not only as teacher's tools in teaching some concepts in science and social studies, but also as pupils' tools in learning the concepts in the two mentioned disciplines. An experimental technique was used in this study where two sets of comparable classes in social studies and science were taped in both non-Tagalog and Tagalog regions. Based on the findings of this study, it can be concluded that Filipino is the more effective medium in social studies, and either Filipino or English can be used as medium of instruction in science with equal effectiveness.
v.1. The research design -- v.2. Verbal interaction in English and Filipino... in grade one / Martha A. Mogul -- v.3. Verbal interaction in English and Filipino ... in grade three / Ester E. Tuy -- v.4. Verbal interaction in English and Filipino ... in grade five / Luis T. Santos, Jr. -- v.5 Verbal interaction in English and Filipino ... in first year high school classes / Corazon Esclabanan -- v.6. [Summary, results, conclusions, recommendations].
Mimeographed.
Thesis (Ph.D.)--University of the Philippines, Quezon City.
Keywords: Science -- Study and teaching (Elementary) -- Philippines; English language; Language and education -- Philippines; Pilipino language; Social sciences -- Study and teaching (Elementary) -- Philippines